若给定条件表达式(M)?(a++):(a--)则下列选项中和表达式M等价的是()。
A: A、(M==0)
B: B、(M==1)
C: C、(M!=0)
D: D、(M!=1)
A: A、(M==0)
B: B、(M==1)
C: C、(M!=0)
D: D、(M!=1)
C
举一反三
- 若给定条件表达式(M)?(a++):(a--)则下列选项中和表达式M等价的是()。 A: A、(M==0) B: B、(M==1) C: C、(M!=0) D: D、(M!=1)
- 若给定条件表达式()?(a++):(a--),则表达式m和( )等价。 A: (m==0) B: (m==1) C: (m!=0) D: (m!=1)
- 给定条件表达式(m)?(a++):(a--),则其中表达式m和_______等价? A: (m!=0) B: (m!=1) C: (m= =0) D: (m= =1)
- 若给定条件表达式(m)?(a++):(a--),则其中表达式m()。? 和(m==1)等价|和(m!=0)等价|和(m!=1)等价|和(m==0)等价
- 若给定条件表达式(m)?(a++):(a--),则其中表达式m()。 A: 和(m==0)等价 B: 和(m!=0)等价 C: 和(m==1)等价 D: 和(m!=1)等价
内容
- 0
若给定条件表达式(M)?(a++):(a--),则其中表达式M( )。 A: 和(M==0)等价 B: 和(M!=1)等价 C: 和(M==1)等价 D: 和(M!=0)等价
- 1
若给定条件表达式(m)?(a++):(a--),则其中表达式m()。 A: 和(m==0)等价 B: 和(m!=0)等价 C: 和(m==1)等价 D: 和(m!=1)等价
- 2
若给定条件表达式(m)?(a++):(a--),则其中表达式m()。 A: 和(m==0)等价 B: 和(m!=0)等价 C: 和(m==1)等价 D: 和(m!=1)等价
- 3
若给定条件表达式(m)?(a++):(a--),则其中表达式m()。 A: 和(m==0)等价 B: 和(m!=0)等价 C: 和(m==1)等价 D: 和(m!=1)等价
- 4
若给定条件表达式(M)?(a++):(a--),则其中表达式M( )。 A: 和(M==0)等价 B: 和(M==1)等价 C: 和(M!=0)等价 D: 和(M!=1)等价